Perfectionism as a Predictor of Anxiety in Foreign Language Classrooms among Russian College Students - Kenneth T. Wang; Tatiana M. Permyakova; Marina S. Sheveleva; Emily E. Camp (LED Edizioni Universitarie, 2018)
This study examined perfectionism as a multidimensional personality factor which influences foreign language learning and classroom anxiety. Hierarchical regression analyses confirmed that the two dimensions of perfectionism, adaptive and maladaptive, relate to Foreign Language Classroom Anxiety (FLCA) differently. After controlling for the effects of general anxiety, perceptions of academic performance, and self-reported English fluency, perfectionistic discrepancy (maladaptive aspect) was a significant predictor of FLCA; perfectionistic standards (adaptive aspect) was not. Measures indicated that this multidimensional nature of perfectionism affects Russian students in the context of foreign language classroom anxiety. Implications regarding the prevention and intervention of maladaptive perfectionism among students are discussed, as well as directions for future studies. These findings are important for teachers, students, and experts who may interact with FLCA and perfectionism as well as those who may personally experience it. The possible strategies to reduce anxiety could include discussing unrealistic beliefs and expectations with reference to foreign language learning, accepting mistakes as an integral part of foreign language learning as well as coaching.